2013
DOI: 10.1002/jbm.b.32953
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer scaffold of electrospun PLA–PCL–collagen nanofibers as a dural substitute

Abstract: Dural closure after the neurosurgery can prevent postoperative complications. Although many types of dural substitute have been developed, most of them lack functional and structural characteristics compared with the natural dura mater. In this study, we used electrospinning method to fabricate a multilayer scaffold to promote dural repair. The inner layer of the scaffold that faces the brain tissue is composed of poly-lactic acid (PLA) to reduce tissue adhesion. The middle layer of the scaffold is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…The basic mechanical performance of the biomimetic patch showed that among transverse and longitudinal directions, the tensile strength ranged from 2.8 to 4.3 Mpa and showed no significant difference ( P = 0.4716, n = 8). Combining the transverse and longitudinal results, the average tensile strength was 4.14 ± 0.18 Mpa ( n = 8), the average stretching elongation was 60.5 ± 13.2% ( n = 8), and the average stitch tear load was 3.71 ± 0.46 N ( n = 8), with all samples having a stitch tear load of >1 N. Compared with the low mechanical properties of collagen matrix substitutes , the tensile strength of this biomimetic patch can be sutured to the dogs' dural mater easily without CSF leakage.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The basic mechanical performance of the biomimetic patch showed that among transverse and longitudinal directions, the tensile strength ranged from 2.8 to 4.3 Mpa and showed no significant difference ( P = 0.4716, n = 8). Combining the transverse and longitudinal results, the average tensile strength was 4.14 ± 0.18 Mpa ( n = 8), the average stretching elongation was 60.5 ± 13.2% ( n = 8), and the average stitch tear load was 3.71 ± 0.46 N ( n = 8), with all samples having a stitch tear load of >1 N. Compared with the low mechanical properties of collagen matrix substitutes , the tensile strength of this biomimetic patch can be sutured to the dogs' dural mater easily without CSF leakage.…”
Section: Resultsmentioning
confidence: 92%
“…To avoid previously encountered complications, Medprin Biotech GmbH developed a biodegradable nonwoven substitute composed of Poly‐L‐lactide (PLLA) fibers with open, highly interconnected pores to create the unique 3D structure that facilitates cell infiltration and tissue generation, and is gradually absorbed by the body. Besides, the PLLA has been shown to be fully compatible with dural tissue and can also reduce tissue adhesion . The objective of this study was to test the safety and effectiveness of this biomimetic patch for dural repair.…”
mentioning
confidence: 99%
“…Electrospinning which uses electrical forces to generate polymeric fibers with nano-/micro-sized diameters is an effective, cost efficient, and easily applied technique [23,24]. Electrospun fibers have been successfully used in drug delivery, tissue engineering, and other biomedical applications due to their highly porous structures, high surface area to volume ratio, potential biocompatibility, and high functionality [25][26][27]. In the literature, although there are limited studies based on coating of Ti implants with electrospun fibers, to the best of our knowledge, no investigation has been demonstrated for PEO nanofiber-coated implant surfaces in terms of cellular/bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…In another set of experiments, we studied the adhesion and growth of human keratinocytes on nanofibrous membranes made of poly-ε-caprolactone (PCL) and its copolymer with PLA (PLA/PCL, ratio 70:30). PCL and PLA/PCL copolymers have been experimentally used for vascular tissue engineering, particularly for replacement of small caliber blood vessels [31,32], neural tissue engineering, specifically for generation of conductive sheaths for neurite outgrowth [104], for substituting the dura mater [105], and also for bone tissue engineering in order to mimic hemi-osteons and to control the spatial organization of osteoblasts [106]. These applications of PCL and PLA/PCL were enabled, among others, by suitable mechanical properties of these polymers, particularly in case of PLA/PCL.…”
Section: Nanofibers In Skin Tissue Engineeringmentioning
confidence: 99%